All solid state battery

The all-solid-state battery design addresses the limited capacity issue by incorporating differential thickness electrode layers with both positive and negative active materials, resulting in enhanced capacity and reliability.

JP7665317B2Active Publication Date: 2025-04-21TAIYO YUDEN KK
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020188242
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-11
Publication Date
2025-04-21
Estimated Expiration
2040-11-11

AI Technical Summary

Technical Problem

Small, non-polar all-solid-state batteries have limited capacity, and there is a need to increase their capacity while maintaining reliability and safety.

Method used

The all-solid-state battery design includes a first electrode layer with both positive and negative electrode active materials, a solid electrolyte layer, and a second electrode layer with varying thickness compared to the first electrode layer, allowing for differential capacity distribution and increased overall capacity.

Benefits of technology

This design effectively increases the capacity of the all-solid-state battery by optimizing the thickness and composition of the electrode layers, while ensuring reliability and safety through balanced capacity distribution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665317000002
    Figure 0007665317000002
  • Figure 0007665317000003
    Figure 0007665317000003
  • Figure 0007665317000004
    Figure 0007665317000004
Patent Text Reader

Abstract

To increase the capacity of an all-solid battery.SOLUTION: An all-solid battery has: a laminate in which a plurality of first electrode layers including positive electrode active material and negative electrode active material, solid electrolyte layers, and second electrode layers including the positive electrode active material and the negative electrode active material and different in thickness from the first electrode layers are laminated, and includes a first surface on which the first electrode layers appear, and a second surface on which the second electrode layers appear; a first external electrode that is provided on the first surface and connected with the first electrode layers; and a second external electrode that is provided on the second surface and connected with the second electrode layers.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an all-solid-state battery. [Background technology]

[0002] In recent years, secondary batteries have been used in various fields. Secondary batteries using electrolytes have problems such as electrolyte leakage. Therefore, all-solid-state batteries that have a solid electrolyte and other components made of solids are being developed.

[0003] In order to confirm the reliability and safety of all-solid-state batteries, short-circuit tests are sometimes performed. In the short-circuit tests, the electrical resistance of the battery is measured to check whether the battery is short-circuited.

[0004] If the polarity of the battery is incorrect during a short circuit test, unexpected carrier movement occurs, resulting in deterioration of the battery characteristics. In order to prevent this, a non-polar all-solid-state battery has been proposed in which both the positive and negative electrodes contain both a positive electrode active material and a negative electrode active material (see, for example, Patent Document 1). Also proposed is a non-polar all-solid-state battery in which both the positive and negative electrodes contain an active material that has the functions of both a positive electrode active material and a negative electrode active material (see, for example, Patent Document 2). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2011-216235 A [Patent Document 2] International Publication No. 2019 / 093404 [Non-patent literature]

[0006] [Non-Patent Document 1] 60th Battery Conference Abstracts 3G19 Summary of the Invention [Problem to be solved by the invention]

[0007] However, small non-polar all-solid-state batteries mounted on wiring boards and the like have a small capacity, and there is room for improvement in terms of increasing the capacity.

[0008] The present invention has been made in consideration of the above problems, and has an object to increase the capacity of an all-solid-state battery. [Means for solving the problem]

[0009] The all-solid-state battery according to the present invention is characterized in having a laminate in which a first electrode layer containing a positive electrode active material and a negative electrode active material, a solid electrolyte layer, and a second electrode layer containing a positive electrode active material and a negative electrode active material and having a thickness different from that of the first electrode layer are laminated in multiple layers, the laminate having a first surface on which the first electrode layer is exposed and a second surface on which the second electrode layer is exposed, a first external electrode provided on the first surface and connected to the first electrode layer, and a second external electrode provided on the second surface and connected to the second electrode layer.

[0010] In the above all-solid-state battery, when a first capacity determined by a ratio of the positive electrode active material in the first electrode layer and a theoretical capacity per unit weight of the positive electrode active material in the first electrode layer is larger than a second capacity determined by a ratio of the negative electrode active material in the second electrode layer and a theoretical capacity per unit weight of the negative electrode active material in the second electrode layer, the second electrode layer may be thicker than the first electrode layer, and when the first capacity is smaller than the second capacity, the second electrode layer may be thinner than the first electrode layer.

[0011] In the above-described all-solid-state battery, the laminate may further include a third surface that is different from each of the first surface and the second surface and is parallel to each of the first electrode layer and the second electrode layer, a cover layer that covers the third surface, and a marker that is provided on the cover layer and distinguishes between the first external electrode and the second external electrode.

[0012] In the all-solid-state battery, a first gap between the marker and the first external electrode and a second gap between the marker and the second external electrode may be different.

[0013] In the all-solid-state battery, a shape of the marker may be asymmetric with respect to a line perpendicular to a direction from the first external electrode to the second external electrode. Effect of the Invention

[0014] According to the present invention, the capacity of an all-solid-state battery can be increased. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a basic structure of an all-solid-state battery. [Diagram 2] FIG. 2 is a top view of an all-solid-state battery. [Diagram 3] FIG. 2 is an enlarged cross-sectional view of an all-solid-state battery. [Figure 4] FIG. 11 is an enlarged cross-sectional view in which the second electrode layer is made thicker than the first electrode layer. [Diagram 5] FIG. 3 is a cross-sectional view of a laminate before a first external electrode and a second external electrode are formed. [Figure 6] FIG. 11 is a top view showing another example of an all-solid-state battery. [Figure 7] FIG. 11 is a top view illustrating another example of an all-solid-state battery. [Figure 8] 1 is a flowchart of a method for manufacturing an all-solid-state battery according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] (Embodiment) 1 is a schematic cross-sectional view showing the basic structure of an all-solid-state battery 100. The all-solid-state battery 100 is a non-polar all-solid-state battery, and has a laminate 60 in which a plurality of solid electrolyte layers 11, a first electrode layer 12, and a second electrode layer 14 are laminated. In the laminate 60, the solid electrolyte layer 11 is interposed between the first electrode layer 12 and the second electrode layer 14.

[0017] Of these, the first electrode layer 12 and the second electrode layer 14 are both conductive layers containing both a positive electrode active material and a negative electrode active material. There is no particular limitation on the positive electrode active material, but here a material having an olivine type crystal structure is used as the positive electrode active material. An example of such a positive electrode active material is a phosphate containing a transition metal and lithium. The olivine type crystal structure is a crystal that natural olivine has, and can be identified by X-ray diffraction.

[0018] An example of an electrode active material having an olivine crystal structure is LiCoPO4, which contains Co. Phosphates in which the transition metal Co is substituted in this chemical formula may also be used. Here, the ratio of Li and PO4 may vary depending on the valence. Co, Mn, Fe, Ni, etc. may also be used as the transition metal.

[0019] The negative electrode active material may be, for example, any one of titanium oxide, lithium titanium composite oxide, lithium titanium composite phosphate, carbon, and lithium vanadium phosphate.

[0020] In this way, by using both the positive electrode active material and the negative electrode active material in each of the first electrode layer 12 and the second electrode layer 14, the similarity between the electrode layers 12, 14 is increased. As a result, each of the first electrode layer 12 and the second electrode layer 14 functions as both a positive electrode and a negative electrode, and even if the terminals of the all-solid-state battery 100 are attached in the reversed polarity, no malfunction occurs during a short circuit test and the battery can withstand practical use.

[0021] When the first electrode layer 12 and the second electrode layer 14 are produced, a conductive assistant such as an oxide-based solid electrolyte material, carbon, or a metal may be added to these electrode layers. Examples of the metal of the conductive assistant include Pd, Ni, Cu, and Fe. Furthermore, an alloy of these metals may be used as the conductive assistant.

[0022] Furthermore, the layer structure of the first electrode layer 12 and the second electrode layer 14 is not particularly limited. For example, as shown in the dotted circle, the first electrode layer 12 may be formed on both main surfaces of a first current collector layer 12b made of a conductive material. Similarly, the second electrode layer 14 may be formed on both main surfaces of a second current collector layer 14b made of a conductive material.

[0023] On the other hand, the material of the solid electrolyte layer 11 is, for example, a phosphate-based solid electrolyte having a NASICON structure. The phosphate-based solid electrolyte having a NASICON structure has high ionic conductivity and is chemically stable in the air. The phosphate-based solid electrolyte is not particularly limited, but a phosphate containing lithium is used here. The phosphate is, for example, a salt based on a composite lithium phosphate salt with Ti (LiTi2(PO4)3), with some of the lithium being substituted with a trivalent transition metal such as Al, Ga, In, Y, or La to increase the Li content. Examples of such salts include Li 1+x Al x Ge 2-x (PO4)3, Li 1+x Al x Zr 2-x (PO4)3, and Li 1+x Al x Ti 2-x (PO4)3 and other Li-Al-M-PO4 phosphates (where M is Ge, Ti, Zr, etc.).

[0024] Also, Li-Al-Ge-PO4-based phosphate to which a transition metal contained in the phosphate in the first electrode layer 12 has been added in advance may be used as the material for the solid electrolyte layer 11. For example, when the first electrode layer 12 contains a phosphate containing either Co or Li, the solid electrolyte layer 11 may contain Li-Al-Ge-PO4-based phosphate to which Co has been added in advance. This makes it possible to suppress the elution of the transition metal from the first electrode layer 12 into the solid electrolyte layer 11.

[0025] Such a laminate 60 has a first surface 60a and a second surface 60b parallel to the lamination direction Z of the first electrode layer 12 and the second electrode layer 14. Of these, the solid electrolyte layer 11 and the first electrode layer 12 are exposed on the first surface 60a. A first external electrode 40a is further provided on the first surface 60a, and the first electrode layer 12 is connected to the first external electrode 40a.

[0026] On the other hand, the second surface 60b faces the first surface 60a, and exposes the solid electrolyte layer 11 and the second electrode layer 14. The second surface 60b is provided with a second external electrode 40b, and the second electrode layer 14 is connected to the second external electrode 40b.

[0027] Furthermore, the laminate 60 has a third surface 60c and a fourth surface 60d parallel to the first electrode layer 12 and the second electrode layer 14, respectively. The third surface 60c is the upper surface that becomes the upper side when the all-solid-state battery 100 is mounted on a wiring board. The fourth surface 60d is the lower surface that becomes the lower side when mounted.

[0028] In this example, a cover layer 19 is formed on each of the third surface 60c and the fourth surface 60d to protect the first electrode layer 12 and the second electrode layer 14 from the atmosphere. The material of the cover layer 19 is not particularly limited, but the same material as the solid electrolyte layer 11 can be used as the material of the cover layer 19.

[0029] The all-solid-state battery 100 described above is a non-polar battery in which each of the first electrode layer 12 and the second electrode layer 14 contains both a positive electrode active material and a negative electrode active material as described above. However, in this embodiment, the ratio of the area occupied by the positive electrode active material in the cross section of the first electrode layer 12 is made larger than the ratio of the area occupied by the positive electrode active material in the cross section of the second electrode layer 14. As a result, the first external electrode 40a side becomes a positive electrode, and the second external electrode 40b side becomes a negative electrode. The capacity of the all-solid-state battery 100 can be made larger than when the first external electrode 40a side is used as a negative electrode and the second external electrode 40b side is used as a positive electrode. In this example, the polarities of the first external electrode 40a and the second external electrode 40b are determined based on the area ratio, but these polarities may be determined by adopting a weight ratio or a molar ratio.

[0030] Although the all-solid-state battery 100 is a non-polar battery, it has a suitable polarity for obtaining such a large capacity. Therefore, in this example, a marker 70 for distinguishing the first external electrode 40a from the second external electrode 40b is provided on the cover layer 19 on the third surface 60c side. The position and shape of the marker 70 can be confirmed by a camera or by visual inspection, and the first external electrode 40a and the second external electrode 40b can be distinguished based on the position and shape. The thickness of the marker 70 is not particularly limited, but is set to about 5 μm to 20 μm in this embodiment. This makes it possible to prevent the marker 70 from cracking or peeling off when the marker 70 is fired. In addition, the marker 70 may be connected to either the first external electrode 40a or the second external electrode 40b, or may not be connected to both the external electrodes 40a and 40b.

[0031] In order to easily recognize the marker 70, it is preferable that the marker 70 has a color different from that of the cover layer 19. For example, when the cover layer 19 is white, adding carbon to the marker 70 to change its color to black creates a clear brightness difference between the marker 70 and the cover layer 19, making it easier to recognize the marker 70 by camera or visual inspection. If the marker 70 can be recognized without adding carbon, it is not necessary to add carbon to the marker 70. In this example, the marker 70 is made of a material different from that of the cover layer 19 and the external electrodes 40a, 40b. The marker 70 may be made of a material different from that of each of the first electrode layer 12 and the second electrode layer 14.

[0032] 2 is a top view of the all-solid-state battery 100. As shown in FIG. 2, in this embodiment, the marker 70 is brought closer to the first external electrode 40a in a top view, so that the marker 70 points to the first external electrode 40a. In this case, the distance L1 between the first external electrode 40a and the marker 70 is shorter than the distance L2 between the second external electrode 40b and the marker 70. Note that the distances L1 and L2 may each be set to a value greater than 0, so that the marker 70 is spaced apart from each of the external electrodes 40a and 40b.

[0033] The shape of the marker 70 is a rectangle that is symmetrical with respect to a straight line P perpendicular to a direction X extending from the first external electrode 40a to the second external electrode 40b.

[0034] FIG. 3 is an enlarged cross-sectional view of the all-solid-state battery 100. As illustrated in FIG. 3, in this embodiment, the thickness D1 of the first electrode layer 12 is made thicker than the thickness D2 of the second electrode layer 14, so that the thicknesses D1 and D2 are different from each other. As an example, the thickness D1 is about 20 μm to 30 μm, and the thickness D2 is about 5 μm to 15 μm. This makes it possible to increase the capacity of the all-solid-state battery 100 compared to the case where the thickness D1 of the first electrode layer 12 is the same as the thickness D2 of the second electrode layer 14. Note that if the thickness D1 of the first electrode layer 12 is blindly increased, the capacity of the positive electrode side becomes too large compared to the negative electrode side, resulting in an imbalance of capacity between the positive electrode side and the negative electrode side. To avoid this, it is sufficient to determine which of the first electrode layer 12 and the second electrode layer 14 should be made thicker based on the theoretical capacity value as follows.

[0035] First, the theoretical capacity per unit weight of the positive electrode active material is c p (Ah / g), and the density of the positive electrode active material is ρ p (g / cm 3 ) As shown in FIG. 3, the thickness of the first electrode layer 12 is D1 (cm) and the area is S p (cm 2 ) Furthermore, the ratio of the area of ​​the positive electrode active material in the first electrode layer 12 is defined as A p In this case, the first capacitance C of the first electrode layer 12 is p (Ah / g) is c p ×ρ p xD1xS p ×A p It becomes.

[0036] In addition, ratio A p can be calculated by observing a cross section of the first electrode layer 12 parallel to the stacking direction Z (see FIG. 1) by SEM (Scanning Electron Microscope)-EDS (Energy Dispersive X-ray Spectroscopy) mapping and identifying the proportion of elements specific to the positive electrode active material that appear on the cross section.

[0037] Similarly, the theoretical capacity per unit weight of the negative electrode active material is c n(Ah / g), and the density of the negative electrode active material is ρ n (g / cm 3 ) As shown in FIG. 3, the thickness of the second electrode layer 14 is D2 (cm) and the area is S n (cm 2 ) Furthermore, the ratio of the area occupied by the negative electrode active material in the second electrode layer 14 is defined as A n At this time, the second capacitance C of the second electrode layer 14 is n (Ah / g) is c n ×ρ n ×T n ×S n ×A n It becomes.

[0038] In addition, ratio A n can be calculated by observing a cross section of the second electrode layer 14 parallel to the stacking direction Z (see FIG. 1) by SEM-EDS mapping and identifying the proportion of elements specific to the negative electrode active material that appear on the cross section.

[0039] The first capacitance C thus obtained p is the second capacitance C n , by making thickness D2 smaller than thickness D1 as shown in FIG. 3, the difference in capacity between the positive electrode side and the negative electrode side is reduced, and the imbalance in capacity between the positive electrode side and the negative electrode side can be reduced.

[0040] On the other hand, the first capacitance C p is the second capacitance C n In the case where thickness D2 is larger than thickness D1, the difference in capacity between the positive electrode side and the negative electrode side is reduced by making thickness D2 larger than thickness D1, and the imbalance in capacity between the positive electrode side and the negative electrode side can be reduced. Fig. 4 is an enlarged cross-sectional view of the case where thickness D2 is made larger than thickness D1 in this way.

[0041] In addition, the first capacitance C of all the first electrode layers 12 p The total value of C p_all and the second capacitance C of all the second electrode layers 14 n The total value of C n_allThe thicknesses D1 and D2 of the first electrode layer 12 and the second electrode layer 14 may be adjusted so that the difference ΔC between them is as small as possible. p_all The imbalance in capacity between the positive electrode side and the negative electrode side may be reduced by adjusting the thicknesses D1, D2 of the first electrode layer 12 and the second electrode layer 14, respectively, so that the difference is within ±15%, more preferably within ±5%.

[0042] Fig. 5 is a cross-sectional view of the laminate 60 before the first external electrode 40a and the second external electrode 40b are formed. As illustrated in Fig. 5, before the external electrodes 40a, 40b are formed, the first electrode layer 12 is exposed on the first surface 60a, and the second electrode layer 14 is exposed on the second surface 60b.

[0043] At this time, in this embodiment, since the thicknesses D1, D2 of the electrode layers 12, 14 are different as described above, the thicknesses of the electrode layers 12, 14 exposed on each surface 60a, 60b are also different. Therefore, even if the marker 70 is peeled off by an external force or the like before the external electrodes 40a, 40b are formed, the polarity of the all-solid-state battery 100 can be determined by a camera or an operator visually checking the difference in the thicknesses of the electrode layers 12, 14 exposed on each surface 60a, 60b.

[0044] Fig. 6 is a top view showing another example of the all-solid-state battery. In the example of Fig. 6, the distance L2 is made smaller than the distance L1, and the marker 70 is moved closer to the second external electrode 40b, so that the marker 70 points to the second external electrode 40b.

[0045] Fig. 7 is a top view showing another example of an all-solid-state battery. In the example of Fig. 7, a triangular marker 70 is provided at approximately the center of the all-solid-state battery 100 in a top view. The apex 70a of the marker 70 is directed toward the first external electrode 40a, so that the marker 70 points to the first external electrode 40a.

[0046] In this case, the shape of the marker 70 is asymmetric with respect to a straight line P perpendicular to a direction X from the first external electrode 40a to the second external electrode 40b. Such asymmetry allows a person or a camera to distinguish between the first external electrode 40a and the second external electrode 40b.

[0047] Next, a method for producing the all-solid-state battery according to this embodiment will be described. Fig. 8 is a flowchart showing the method for producing the all-solid-state battery according to this embodiment.

[0048] (Ceramic raw powder production process) First, a powder of the phosphate-based solid electrolyte constituting the above-mentioned solid electrolyte layer 11 is prepared. For example, the raw material and additives are mixed, and a solid-phase synthesis method or the like is used to prepare the powder of the phosphate-based solid electrolyte constituting the solid electrolyte layer 11. The obtained powder can be dry-pulverized to adjust to a desired average particle size. For example, the desired average particle size is adjusted using a planetary ball mill using 5 mmφ ZrO2 balls.

[0049] The additives include sintering aids, such as Li-BO based compounds, Li-Si-O based compounds, Li-CO based compounds, Li-SO based compounds, and Li-PO based compounds.

[0050] (Green sheet production process) Next, the obtained powder is uniformly dispersed in an aqueous or organic solvent together with a binder, a dispersant, a plasticizer, etc., and wet-pulverized to obtain a solid electrolyte slurry having a desired average particle size. In this case, a bead mill, a wet jet mill, various kneaders, a high-pressure homogenizer, etc. can be used, and it is preferable to use a bead mill from the viewpoint of simultaneously adjusting the particle size distribution and dispersing.

[0051] Then, a binder is added to the obtained solid electrolyte slurry to obtain a solid electrolyte paste. A green sheet for the solid electrolyte layer 11 is obtained by coating the solid electrolyte paste. A green sheet for the cover layer 19 can be produced in the same manner. The coating method is not particularly limited, and a slot die method, a reverse coat method, a gravure coat method, a bar coat method, a doctor blade method, or the like can be used. The particle size distribution after wet pulverization can be measured, for example, using a laser diffraction measurement device using a laser diffraction scattering method.

[0052] (Electrode layer paste preparation process) Next, an electrode layer paste is prepared for producing the first electrode layer 12 and the second electrode layer 14. For example, the positive electrode active material, the negative electrode active material, and the solid electrolyte material are highly dispersed in a bead mill or the like to prepare a ceramic paste consisting only of ceramic particles. Alternatively, a carbon paste containing carbon particles such as carbon black may be prepared, and the carbon paste may be kneaded into the ceramic paste.

[0053] (Marker paste production process) Next, a marker paste is prepared for producing the above-mentioned marker 70. Here, the marker paste is prepared by kneading ceramic particles with carbon particles such as carbon black.

[0054] (Lamination process) First, a paste for an electrode layer is printed on one main surface of a green sheet. Next, the printed green sheets are alternately shifted and stacked to obtain a laminate 60. After that, a plurality of green sheets for a cover layer 19 are stacked on each of the third surface 60c and the fourth surface 60d of the laminate 60, and a paste for a marker 70 is printed on the topmost green sheet.

[0055] (Firing process) Next, the laminate 60 is fired in a firing atmosphere containing oxygen. In order to suppress the loss of the carbon material contained in the electrode layer paste, the oxygen partial pressure of the firing atmosphere is set to 2×10 -13On the other hand, in order to suppress the melting of the phosphate-based solid electrolyte, it is preferable to set the oxygen partial pressure to 5×10 -22 It is preferable to set the pressure at 1000 MPa or more.

[0056] Thereafter, a metal paste is applied to each surface 60a, 60b of the laminate 60 and baked to form the first external electrode 40a and the second external electrode 40b. The first external electrode 40a and the second external electrode 40b may also be formed by sputtering or plating. With the above steps, the basic structure of the all-solid-state battery 100 is completed. EXAMPLES

[0057] Example 1 All-solid-state batteries according to Examples 1 to 5 and Comparative Example 1 were fabricated as follows. First, Co3O4, Li2CO3, ammonium dihydrogen phosphate, Al2O3, and GeO2 were mixed together to prepare a solid electrolyte material powder containing a specified amount of Co. 1.3 Al 0.3 Ge 1.7 (PO4)3 was prepared by solid-phase synthesis. The obtained powder was dry-milled with ZrO2 balls. A solid electrolyte slurry was then prepared by wet-milling using ion-exchanged water or ethanol as a dispersion medium. A binder was added to the obtained slurry to obtain a solid electrolyte paste, and a green sheet was then prepared. LiCoPO4, Li containing a specified amount of Co, 1.3 Al 0.3 Ti 1.7 (PO4)3 was synthesized by solid-phase synthesis as described above.

[0058] In Examples 1 to 5, the positive electrode active material, the negative electrode active material, and the solid electrolyte material were highly dispersed using a wet bead mill or the like to prepare a ceramic paste consisting only of ceramic particles. Next, the ceramic paste and a conductive assistant were thoroughly mixed to prepare an electrode layer paste for producing the first electrode layer 12 and the second electrode layer 14.

[0059] The positive electrode active material was LiCoPO4. The negative electrode active material was Li 1+x Al x Ti2-x (PO4)3 was used. The electrode layer paste was prepared so that the ratio of the area occupied by the positive electrode active material in the cross section of the first electrode layer 12 after firing was greater than the ratio of the area occupied by the positive electrode active material in the cross section of the second electrode layer 14.

[0060] A paste for electrode layers was printed on the green sheets by screen printing. Eleven of the printed green sheets were stacked, shifted so that the electrodes were pulled out to the left and right, to produce a laminate 60. A plurality of green sheets were attached to the top and bottom of the laminate 60 as cover layers 19. The green sheets were then compressed by a hot press, and the laminate 60 was cut to a predetermined size by a dicer.

[0061] The cut laminate 60 was degreased by heat treatment at 300° C. to 500° C., and sintered by heat treatment at 900° C. or less. The cross section of the sintered laminate 60 was observed with an SEM to identify the regions where the conductive additive was present. The regions were identified as the first electrode layer 12 and the second electrode layer 14, and the thicknesses of these electrode layers 12 and 14 were measured.

[0062] As a result, in Example 1, the thickness D1 of the first electrode layer 12 was 10 μm, and the thickness D2 of the second electrode layer 14 was 12 μm.

[0063] Example 2 In Example 2, the thickness D1 of the first electrode layer 12 was 10 μm, and the thickness D2 of the second electrode layer 14 was 15 μm.

[0064] Example 3 In Example 3, the thickness D1 of the first electrode layer 12 was 10 μm, and the thickness D2 of the second electrode layer 14 was 20 μm.

[0065] Example 4 In Example 4, the thickness D1 of the first electrode layer 12 was 10 μm, and the thickness D2 of the second electrode layer 14 was 50 μm.

[0066] Example 5 In Example 5, the thickness D1 of the first electrode layer 12 was 10 μm, and the thickness D2 of the second electrode layer 14 was 100 μm.

[0067] Comparative Example 1 In the comparative example, only a positive electrode active material was used as the electrode active material of the first electrode layer 12, and no negative electrode active material was used. Also, only a negative electrode active material was used as the electrode active material of the second electrode layer 14, and no positive electrode active material was used. As a result, the all-solid-state battery according to the comparative example is not a non-polar battery, but a battery having polarity. The thickness D1 of the first electrode layer 12 was 10 μm, and the thickness D2 of the second electrode layer 14 was 10 μm.

[0068] Next, the capacity of the all-solid-state batteries was examined for Examples 1 to 5 and Comparative Example 1. In addition, whether the polarity of the all-solid-state battery can be determined by visually checking the thickness of each electrode layer 12, 14 when the marker 70 is peeled off was also examined for Examples 1 to 5 and Comparative Example 1. The results are shown in Table 1.

[0069] [Table 1] In Table 1, "Each capacitance C p , C n The larger of the two is the first capacitance C p and the second capacitance C n Indicates which is larger.

[0070] The "polarity during short circuit inspection" was marked with "◯" if the polarity was reversed during short circuit inspection and marked with "X" if the polarity was reversed during short circuit inspection and was ... not reversible.

[0071] For "distinguishing polarity by appearance," a "good" was given if the polarity could be easily distinguished by visually checking the difference between the thicknesses D1 and D2 of the first electrode layer 12 and the second electrode layer 14, and a "△" was given if it was not easy but still possible to distinguish. Also, a "bad" was given if the polarity could not be distinguished even by visually checking the difference between the thicknesses D1 and D2.

[0072] The "capacity" was calculated as follows. First, the discharge capacity Q (mAh) at A-0.5 (V) was measured. Next, charging was performed at a constant current I, and the voltage change ΔV between the external electrodes 40a, 40b immediately after the start of charging was measured. The resistance R (= ΔV / I) thus obtained was multiplied by the discharge capacity Q to obtain the capacity C (mAh·Ω). If the capacity C was 2500 mAh·Ω or more, it was marked as "Good", and if the capacity C was 1000 mAh·Ω or more but less than 2500, it was marked as "Good". And if the capacity C was less than 1000 mAh·Ω, it was marked as "Poor".

[0073] The "overall evaluation" was marked as "X" if at least one of "inspection during short circuit", "determination of polarity by appearance", and "capacity" was marked as "X". The "overall evaluation" was marked as "△" if none of "inspection during short circuit", "determination of polarity by appearance", and "capacity" were marked as "X", but not all of them were marked as "O". And if "inspection during short circuit", "determination of polarity by appearance", and "capacity" were all marked as "O", the "overall evaluation" was also marked as "O".

[0074] As shown in Table 1, in Example 1, the first electrode layer 12 and the second electrode layer 14 each contain a positive electrode active material and a negative electrode active material, so that the all-solid-state battery 100 is non-polar and the "polarity during short circuit inspection" is "◯". This is also true for Examples 2 to 5.

[0075] In addition, the "discrimination of polarity by appearance" of Example 1 was rated as "△" because the difference in thickness between the electrode layers 12 and 14 was small at 2 μm, but the difference was visible. The "capacity" was rated as "◯". As a result, the "overall evaluation" of Example 1 was rated as "△".

[0076] On the other hand, in Example 2, the difference in thickness between the electrode layers 12 and 14 was as large as 5 μm, so the "discrimination of polarity by appearance" was rated as "good." The "capacity" of Example 2 was also rated as "good." As a result, the "overall evaluation" of Example 2 was rated as "good."

[0077] Similarly, in Example 3, both the "discrimination of polarity by appearance" and the "capacity" were rated "good", and the "overall evaluation" was also rated "good".

[0078] In Example 4, the difference in thickness between the electrode layers 12 and 14 was as large as 40 μm, so the "discrimination of polarity by appearance" was rated as "good". However, the "capacity" was rated as "good". As a result, the "overall evaluation" of Example 4 was rated as "good".

[0079] In Example 5, the difference in thickness between the electrode layers 12 and 14 was as large as 90 μm, so the “discrimination of polarity by appearance” was rated as “good”, but the “capacity” was rated as “good”. As a result, the “overall evaluation” of Example 5 was also rated as “good”.

[0080] On the other hand, since the all-solid-state battery according to Comparative Example 1 is a battery with polarity as described above, the "polarity during short circuit inspection" was rated "x". In addition, since there is no difference in thickness between the electrode layers 12 and 14 in Comparative Example 1, the "polarity determination by appearance" was also rated "x". Furthermore, the "capacity" was rated "x", and the "overall evaluation" was rated "x".

[0081] Although the embodiments of the present invention have been described in detail above, the present invention is not limited to such specific embodiments, and various modifications and variations are possible within the scope of the gist of the present invention described in the claims. [Explanation of symbols]

[0082] 11: Solid electrolyte layer 12: First electrode layer 14: Second electrode layer 19: Cover layer 40a: First external electrode 40b: second external electrode 60: Laminate 70: Marker 100: All-solid-state battery

Claims

1. a laminate including a first electrode layer including a positive electrode active material and a negative electrode active material, a solid electrolyte layer, and a second electrode layer including a positive electrode active material and a negative electrode active material and having a thickness different from that of the first electrode layer, the laminate having a first surface on which the first electrode layer is exposed and a second surface on which the second electrode layer is exposed; a first external electrode provided on the first surface and connected to the first electrode layer; a second external electrode provided on the second surface and connected to the second electrode layer; having when a first capacity determined by a ratio of the positive electrode active material in the first electrode layer and a theoretical capacity per unit weight of the positive electrode active material in the first electrode layer is larger than a second capacity determined by a ratio of the negative electrode active material in the second electrode layer and a theoretical capacity per unit weight of the negative electrode active material in the second electrode layer, the second electrode layer is thicker than the first electrode layer, When the first capacity is smaller than the second capacity, the second electrode layer is thinner than the first electrode layer.

2. the laminate has a third surface that is different from each of the first surface and the second surface and is parallel to each of the first electrode layer and the second electrode layer; a cover layer covering the third surface; The all-solid-state battery according to claim 1 , further comprising a marker provided on the cover layer for distinguishing the first external electrode from the second external electrode.

3. 3. The all-solid-state battery according to claim 2, wherein a first distance between the marker and the first external electrode is different from a second distance between the marker and the second external electrode.

4. 3. The all-solid-state battery according to claim 2, wherein the shape of the marker is asymmetric with respect to a straight line perpendicular to a direction from the first external electrode to the second external electrode.

Citation Information

Patent Citations

  • Lithium-ion secondary battery and its manufacturing method

    JP2010140725A

  • Lithium ion secondary battery

    JP2011216235A

  • Lithium ion secondary battery

    JP2013004421A

  • All-solid power storage element

    JP2013243112A

  • All-solid-state battery

    JP2020053307A